Orthography as Described in Latin Grammars and Spelling in Latin Epigraphic Texts - Gaspar, Catarina (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper examines writing and orthography in the work of Latin grammarians and spelling variants in epigraphic texts. It focuses on the uses of the letter H and the spelling of the word sepulchrum. The word’s spelling seems to be connected to the spelling of other words through the adjective pulcher, pulchra, pulchrum. The analysis indicates that the teaching and learning of orthography had a limited influence on epigraphic texts, but there is evidence of the consistently high frequency of the spelling sepulcrum. The paper also shows how data on Latin orthography can help in understanding the chronology of the evolution of spelling in epigraphic texts.